Tracking the Formation of a Polynuclear Co16 Complex and Its Elimination and Substitution Reactions by Mass Spectroscopy and Crystallography - Hu, Yue-Qiao; Zeng, Ming-Hua; Zhang, Kun; Hu, Sheng; Zhou, Fu-Fang; Kurmoo, Mohamedally (Journal of the American Chemical Society, 2013)
We present the syntheses and structures of the biggest chiral cobalt coordination cluster, [Co16(L)4(H3L)8(N3)6](NO3)2·​16H2O·​2CH3OH (1, where H4L = S,S-1,2-bis(1H-benzimidazol-2-yl)-1,2-ethanediol). 1 consists of two Co4O4 cubes (Co4(L)2(H3L)2) alternating with Co2(EO-N3)2Co2 (Co4(L)2(H3L)2(N3)2), bridged by the benzimidazole and azide nitrogen atoms to form a twisted ring. The ligand adopts both cis and trans forms, and all the rings have the same chiralilty. ESI-MS of 1 from a methanol solution of crystals reveals the fragment [Co16(L)4(H3L)8(N3)6+2H]4+, suggesting the polynuclear core is stable in solution. ESI-MS measurements from the reaction solution found smaller fragments, [Co4(H3L)4–H]3+, [Co4(H3L)4–2H]2+, [Co4(H3L)4(N3)2]2+, and [Co2(H3L)2]2+, and ESI-MS from a methanol solution of the solid deposit found in addition the Co16 core. These results and the dependence on the synthesis time allow us to propose the process for the formation of 1, which opens up a new way for the direct observation of the ligand-controlled assembly of clusters. In addition, the isolation of [Co4(H3L)4](NO3)4·​4H2O (2) consisting of separate Co4O4 cubes with the ligands being only cis in crystalline form supports the proposal. Interestingly, N3  is replaced by either CH3O– or OH–, and this is the first time that high-resolution ESI-MS is successfully utilized to examine both the step-by-step elimination and substitution of inner bridging ligands in such a high nuclear complex. Increasing the voltage results in stepwise elimination of azide from the parent cluster. The preliminary magnetic susceptibility of 1 indicates ferromagnetic cubes antiferromagnetically coupled to the squares within the cluster, though in a field of 2.5 kOe, weak and slow relaxation is observed below 4 K.